PENGEMBANGAN KETERAMPILAN KEPEMIMPINAN: GAYA KEPEMIMPINAN GENERASI LAMA DAN GENERASI BARU TENTANG MANA YANG PALING IDEAL - Ade Rukmana; Hadi Nurhadi; Irnie Victorynie (STKIP Subang, 2025)
This study explores the differences in leadership styles across three generations Baby Boomers, Millennials, and Generation Z within the context of educational institutions. Using a qualitative case study method and in-depth interviews with two school principals representing different generations, the research finds significant contrasts in leadership values, communication approaches, and decision-making strategies. Baby Boomers tend to favor hierarchical, formal, and experience-based leadership, while Millennials and Gen Z prefer collaborative, flexible, and digitally driven leadership practices. These differences stem from social, cultural, and technological contexts that shaped each generation. Furthermore, the study identifies a mismatch between conventional leadership training programs and the learning preferences of younger generations. It is recommended that organizations adopt leadership development strategies that are generationally responsive, emphasizing digital literacy, emotional intelligence, and experiential learning. Intergenerational synergy can be achieved when leadership training is tailored to accommodate both traditional values and modern expectations. Keywords: Intergenerational leadership, Millennials, Gen Z, leadership development, educational management.